Biodiversity characteristics of small high-altitude tropical man-made reservoirs in the Eastern Rift Valley, Kenya - Wamicha, Wellington N; Mavuti, Kenneth M.; Mwaura, Francis (University Of Nairobi, 2002)
The biodiversity characteristics in eight small (0.065–0.249 km2) public man-made reservoirs in the central part of the Eastern Rift Valley, Kenya, were studied between 1995 and 1998. A total of 71 phytoplankton species belonging to approximately 50 taxa were identified. Chlorophytes and cyanobacteria dominated the crop. The dominant taxa included Botryococcus, Syunura, Microsystis, Anabaena, and Cosmarium. A total of over 40 zooplankton species were identified. The community was composed mainly of crustacea, rotifers and protozoa. The most dominant group was Keratella but Brachionus and Nauplius were equally abundant. The diversity and abundance of benthic invertebrates was not high, and only 18 species were identified throughout the study period with the range of species number being 1–7 per reservoir. The benthic fauna was mainly composed of Lumbriculidae and Chironomid worms. A total of six monthly bird counts found an average of 60 birds per reservoir, and a total of 49 species was identified. Ducks, geese and coots dominated the waterfowl, especially during the dry season. Large-scale breeding by Black-headed Heron (Ardea melanocephala) and Little Egret (Egretta garzetta) was observed in one of the sites, and other species were also breeding in the reservoirs. The population of waterbirds in reservoirs was closely related to the biomass of benthic invertebrates, and the findings of the study indicate that the structure and dynamics of life forms within small man-made reservoirs can serve as excellent sensors and indicators of the state of watershed health.